1997
DOI: 10.1507/endocrj.44.53
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of the Prolactin Receptor Gene Expression in the Mammary Gland of Early Pregnant Mouse.

Abstract: Abstract. The purpose of this research was to examine the hormonal regulation of the PRL receptor (PRL-R) gene expression in the mammary gland of early pregnant mouse. Following reversetranscription, the quantity of PRL-R mRNA was determined by the competitive polymerase chain reaction. The level of long form PRL-R (PRL-RL) mRNA changed cyclically with the highest at estrus and the lowest at diestrus II. PRL-RL mRNA was maintained at high levels for the first 3 days of pregnancy but declined to lower levels on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…In the mammary glands of mice ovariectomized during early pregnancy, both E 2 and PRL upregulate PRLR-LF mRNA expression, while it is suppressed by P (Mizoguchi et al 1997). PRL upregulates PRLR levels in the mammary glands of pseudopregnant rabbits, while P prevents this PRL-induced upregulation (Djiane & Durand 1977).…”
Section: Discussionmentioning
confidence: 94%
“…In the mammary glands of mice ovariectomized during early pregnancy, both E 2 and PRL upregulate PRLR-LF mRNA expression, while it is suppressed by P (Mizoguchi et al 1997). PRL upregulates PRLR levels in the mammary glands of pseudopregnant rabbits, while P prevents this PRL-induced upregulation (Djiane & Durand 1977).…”
Section: Discussionmentioning
confidence: 94%
“…PRL, on the other hand, has been demonstrated to increase estrogen receptor expression in mammary epithelial cells in vitro (7). The estrogen receptor is known to increase both progesterone receptor (PR) and PRL-R expression (11,28). PR signaling is indispensable for the formation of small side branches in terminal duct lobular units and alveologenesis (3,16).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that E2 can increase prolactin receptor expression in both mice and humans in cells outside the immune system [29][30][31]. Results from Figure 2 show that E2 treatment increases prolactin receptor expression in cells of the immune system as well, as both B and CD4 T cells showed significant increases.…”
Section: Discussionmentioning
confidence: 74%